Training on making learning media using Canva to increase teacher creativity - Ita Handayani; Widyah Noviana; Harumi Widihastuti; Rika Handayani (Universitas Muhammadiyah Magelang, 2023)
Community service aims to provide training in making learning media using Canva to increase teacher creativity. This Community Service is conducted at MI AR Rahman Rawakalong, located in Kp. Ciater RT 01/09, Ds. Rawakalong, Kec. Mount Sindur, Bogor. The method of implementing community service is through lectures, training, discussion, and evaluation by the service team by examining the results of learning media in the form of posters, power points, and videos made by the teacher. The results achieved in this community service provide insight and benefits to MI AR Rahman Rawakalong teachers regarding learning media. In addition, Rahman Rawakalong MI AR teachers are able to create posters, power points, and videos using Canva.